2006
DOI: 10.1111/j.1365-2699.2006.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Living in the city: can anyone become an ‘urban exploiter'?

Abstract: Aim  As urban landscapes expand, shifts in biodiversity are occurring. This is leading biogeographers and ecologists to consider human‐dominated landscapes in their current work. One question that arises is: what characterizes those species that are widespread in the most highly urban environments compared with those restricted to less urbanized areas in the city? Here, we aim to identify the traits that enable species to become urban exploiters, i.e. to dominate highly urbanized surroundings. Identifying thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
440
12
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(497 citation statements)
references
References 56 publications
(116 reference statements)
28
440
12
17
Order By: Relevance
“…Many introduced bird species in urban areas around the world are granivores or omnivores, which is ideal for capitalizing on supplementary food resources. In most countries, though, there are also native granivores and omnivores present (32,33)usually the primary targets of feeding-with which introduced species must compete.…”
Section: Discussionmentioning
confidence: 99%
“…Many introduced bird species in urban areas around the world are granivores or omnivores, which is ideal for capitalizing on supplementary food resources. In most countries, though, there are also native granivores and omnivores present (32,33)usually the primary targets of feeding-with which introduced species must compete.…”
Section: Discussionmentioning
confidence: 99%
“…A relação negativa entre o tamanho das espécies -em relação à massa -e a intensidade de urbanização que observamos é oposta ao padrão encontrado em outros estudos (González Oreja et al, 2007;Kark et al, 2007;Croci et al, 2008;Conole & Kirkpatrick, 2011). Ou seja, enquanto em Pelotas as aves tenderam a ser maiores em níveis baixos de urbanização, em outras regiões as aves tenderam a ser menores.…”
Section: Discussionunclassified
“…A urbanização pode ser determinante em alterar ou mesmo suprimir alguns atributos funcionais de assembleias de aves, já que engloba vários fatores de modificação de habitat (Kark et al, 2007;Flynn et al, 2009). Conforme Blair (1996) sugeriu, espécies que conseguem ultrapassar o filtro ambiental imposto pela urbanização intensa podem ser chamadas de "tolerantes urbanos" em contraponto aos "intolerantes urbanos", cujos atributos são incompatíveis com estes ambientes.…”
unclassified
“…This finding is in accordance with the common notion that behavioral flexibility and adopting novel behaviors may be especially adaptive in urban habitats (10,43), although this assumption has not yet been tested within any species to our knowledge. In an interspecific aspect, Sasvári (44) showed that more urbanized species learn faster, whereas Kark et al (45) found no association between the degree of urbanization and innovativeness. Clearly this topic needs more attention.…”
Section: ) But Not In Starlings (Sturnus Vulgaris; Ref 34)mentioning
confidence: 99%